Veterinary parasitology teaching – Ten years of experience with the Vetsuisse curriculum - Schnyder, Manuela; Hertzberg, Hubertus; Mathis, Alexander; Schönmann, Marietta; Hehl, Adrian; Deplazes, Peter (Veterinary parasitology, 2018)
Pursuant to the Joint Declaration by 29 European education ministers in June 1999 in the city of Bologna, Italy, the so-called ‘Bologna Process’ was officially introduced at the Vetsuisse Faculty (Universities of Zurich and Berne) in Switzerland in 2007. The long-term goal of restructuring the study programmes was to create a common European Higher Education Area (EHEA), with uniform and clearly defined standards for degrees (“diplomas”). Accordingly, the Vetsuisse curriculum was organised as a 3-year Bachelor and a 2-year Master study program. For the final Federal examination in veterinary medicine, both programs and a master thesis have to be completed. Parasitology, as a subject, is introduced with selected examples in the ecology course during the first academic year. The second and third years of the Bachelor program comprise non-organ-centred (NOC) and integrated organ-centred (OC) course modules, respectively. In the NOC modules, parasitology is taught in consecutive courses, focussing on topics including occurrence, biology, pathogenesis, clinical manifestations, diagnostics and the strategic principles of therapeutic and prophylactic interventions against major veterinary and zoonotic parasites. This syllabus is complemented with live demonstrations as well as practical laboratory exercises. Lecture notes, with defined learning objectives, are based on the textbook “Parasitology in Veterinary Medicine” which is available free of charge to students as an on-line edition in German. Furthermore, students review relevant parasitoses in the diagnostic context of OC case presentations. In another module, immunological aspects of parasitic diseases are elaborated on group sessions, supported through the use of specialist literature. The two-year Master program is divided into a core syllabus for all students, and elective subjects are chosen from six areas of specialisation (three each with clinical or non-clinical focus). Within the clinically focused specialisations, interactive teaching of control strategies against parasitoses of companion and farm animals is the focus. Students specialising in ‘Pathobiology’ experience a deep immersion in parasitology. Learning objectives are verified in different test formats. E-learning tools, including a learning management on-line platform, allow interactive student training in coproscopic diagnostic techniques and in arachno-entomology and provide case-oriented teaching. Since an aptitude test limits the number of first-year students in veterinary medicine in Switzerland (80 in Zürich, 70 in Berne), the conditions for students and teachers are similar each year. The fragmentation of teaching in veterinary parasitology, the reduction of the number of diagnostic exercises and clinically oriented day-1-skills pertaining to the control of parasitoses are critically commented upon.